Urban South African consumers' ability to discursively reflect on the sustainability of their households' fresh produce consumption and waste practices amidst global concerns about climate change - Erasmus, Alet C. (Aletta Catharina) (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2014.